KONTRIBUSI FATWA MAJELIS ULAMA INDONESIA DALAM PEMBENTUKAN HUKUM POSITIF DI INDONESIA - Ilham Hanafiah Damanik; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
The Republic of Indonesia is a constitutional state, where all actions and behavior mustbe based on law. Muslims in Indonesia often face problems due to technological advancesand times that require legal certainty in accordance with Islamic law. In order to deal withthis problem, the Indonesian Ulema Council as an institution engaged in the field of religionas well as a government partner provides answers through fatwas. Fatwas in positive lawoccupy a position as a source of law and cannot be enforced. Therefore, fatwas must betransformed into positive law.This type of research is normative research, where this research uses a researchmethodology of the legal principles that exist in the formation of legislation, namely theprinciple of openness and the principle of legal certainty. The data source used wassecondary data, with the literature review method, after the data was collected then analyzedto draw conclusions.From the research results, it is concluded that, First, the Indonesian Ulema Council isnot a state institution, it is in the infrastructure element (the socio political sphere), moreprecisely non-governmental organizations (NGOs). Second, the contribution of the MUI fatwain the formation of positive law in Indonesia is quite influential, this can be seen by the birthof various kinds of laws and regulations whose source comes from the MUI fatwa itself,considering the MUI fatwa in Islamic law as a source of law and in positive law in Indonesiacan be categorized as a source of law in the form of legal or religious doctrine / opinion.Keywords: Positive Law - Fatwa - Indonesian Ulema Council